Sintesis Membran Silika Berbahan Baku Sekam Padi Variasi: Massa Silika - Ramadhani, Trie Sucy; Pinem, Jhon Armedi; Amri, Idral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The membrane is a selective and semipermeable layer that is between two phases, namely the feed phase and the permeate phase. The synthesis of silica membrane made from rice husk was carried out using phase inversion method. The purpose of this study was to determine the classification of silica membranes through characterization, determine the effect of variations in silica mass (5, 10, 15, and 20 gram) on the membrane pore, flux, and rejection using variations of operating pressure 1, 2, 3 bars. This study produced a porous membrane. Characterization tests carried out include SEM analysis, flux and rejection. Based on the test characteristics of permeability, selectivity, and pore statistics that have been carried out on the membrane shows that the silica membrane is an ultrafiltration type membrane.Keywords : phase inversion, rhodamin B, semipermiabel, ultrafiltration